High-current-carrying multi-phase electrode with vertical array type carbon nano catalyst layer and controllable preparation method and application of high-current-carrying multi-phase electrode

By constructing a vertical array carbon nanocatalytic layer on the composite electrode and controlling its structure to build a superhydrophobic three-phase interface, the problem of low current efficiency at high current density is solved, and the effect of efficient hydrogen peroxide production is achieved.

CN119592988AActive Publication Date: 2025-03-11NANJING TECH UNIV

Patent Information

Application Number
CN202411787054.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Due to the limited hydrophobicity of the existing composite electrodes, the electron transfer rate is low, the active site is small, and the specific surface area is small, which leads to low current efficiency, low hydrogen peroxide yield and short service life, making it difficult to operate under industrial-grade high current density.

Method used

A high-current-carrying multi-phase composite electrode with a vertical array carbon nanocatalytic layer is used to control the height, diameter and morphology of its structure to build a superhydrophobic three-phase interface to achieve the optimal state of gas-liquid equilibrium, thereby improving the yield and current efficiency of hydrogen peroxide.

Benefits of technology

Under high current density, high yield and utilization of hydrogen peroxide can be achieved, current efficiency can be maintained between 80 and 99%, and electrode stability is good, suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592988A_ABST
    Figure CN119592988A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of composite electrode preparation, and particularly relates to a high-current-carrying multiphase electrode with a vertical array type carbon nano catalyst layer and a controllable preparation method and application of the high-current-carrying multiphase electrode with the vertical array type carbon nano catalyst layer. The vertical array type carbon nano catalyst layers with different structural sizes (adjustable diameter and height) are synthesized by assisting a chemical vapor deposition method, and the multi-phase electrode with different functional layers is prepared on the carbon-based composite carrier through hot pressing. The high-current-carrying multi-phase electrode provided by the invention can realize the purpose of keeping high-electricity hydrogen peroxide production current efficiency under industrial-grade large current (300 mA / cm < 2 >). The composite electrode is mainly used for in-situ electrocatalytic production of hydrogen peroxide, and under the condition of industrial large current (300 mA / cm < 2 >), the concentration of hydrogen peroxide can reach 1-5 wt%, and the current efficiency can be maintained at 80-99%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of composite electrode preparation, and in particular relates to a high current-carrying multiphase electrode with a vertical array carbon nanocatalytic layer and a controllable preparation method and application thereof. Background Art

[0002] Hydrogen peroxide is an inorganic chemical raw material with a wide range of uses and an environmentally friendly and efficient oxidant. It is widely used in pharmaceutical factories, chemical companies, environmental protection, textile bleaching and other industries. In 2018, China's hydrogen peroxide production was 10.29 million tons, a year-on-year increase of 16.5%; in 2019, China's hydrogen peroxide production was 10.75 million tons, a year-on-year increase of 4.5%; in 2020, China's hydrogen peroxide production was 14.67 million tons, a year-on-year increase of 36.5%.

[0003] In order to achieve efficient and large-scale electrosynthesis of H2O2, new composite electrodes have been developed with the advantages of low cost, good availability and excellent performance, which are expected to further improve the selectivity of oxygen reduction reaction to generate high-concentration H2O2. The electrode preparation technology was first used in fuel cells and was discovered by the British Grove in 1839. However, with the extensive use of carbon materials in the late 1970s and the emergence of porous carbon-based materials with low catalyst loading, the production cost of electrodes has been greatly reduced, and its application range has been expanded to achieve electrochemical reduction of various gases including oxygen, carbon dioxide, ammonia, etc.

[0004] Vertical array carbon nanostructures have been a hot topic in recent years due to their unique mechanical, thermal, electrical and optical properties. The huge advantages of vertical arrangement over random orientation are mainly reflected in the fields of nanoelectronics, field emitters, light absorbers, drug delivery systems, gas sensors, water and molecular sieves, and energy storage devices, which have great application prospects.

[0005] Since the discovery of vertical array carbon nanostructures, they have attracted the interest of many researchers and engineers with their unique physical and chemical properties, such as high conductivity and mechanical strength. Because vertical array carbon nanostructures have a higher specific surface area and better performance than traditional electrode materials, they can well improve energy efficiency. By controlling the diameter and density of vertical array carbon nanostructures, as the density increases, the conductivity increases and the gas permeability decreases. As the diameter increases, the dispersion of catalyst nanoparticles improves, the conductivity increases, but the gas permeability decreases. Therefore, the method of separately controlling the diameter and density of vertical array carbon nanostructures is crucial for the application of new electrode materials.

[0006] At room temperature and pressure, the dissolved oxygen saturation in pure water is between 7.5-9.0 mg / L, which limits the reduction of O2 on the electrode surface. The vertical array carbon nanocatalytic layer composite electrode has larger pores and larger specific surface area, which is conducive to promoting the material transfer between the gas-liquid-solid three phases. It can provide gas substances under uninterrupted inflation, and at the same time, it can allow the gas to pass through the pores from the electrolyte into the electrode, thereby greatly improving the mass transfer efficiency, making it superior to the traditional planar electrode.

[0007] In the prior art, when growing vertical array carbon nano catalysts in a CVD tube furnace, a period of low-temperature treatment is required (to vaporize and volatilize the precursor) before high-temperature treatment can be performed. Therefore, the tube furnace needs to be set at a low temperature first and then heated to a high temperature. There is a time interval between the vaporization of the precursor and the growth of the catalyst. At this time, the precursor (carbon source and catalyst) after vaporization cannot immediately start to grow vertical array carbon nano catalyst materials at high temperature, thus causing the catalyst structure to be relatively disordered or making the morphology, diameter, and height of the vertical array structure uncontrollable. Summary of the invention

[0008] The purpose of the present invention is to provide a high current carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer and a controllable preparation method and application thereof, so as to solve the problems that the unimproved electrode is flooded with water due to limited hydrophobicity, low electron transfer rate, few active sites, and small specific surface area, which leads to low current efficiency, low hydrogen peroxide production, short service life and difficulty in industrial-grade high current density (over 100 mA / cm 2 ), and this method is also suitable for large-scale industrial production.

[0009] The high-current-carrying multiphase composite electrode with a vertically arrayed carbon nanocatalytic layer allows gaseous oxygen to pass from the gas phase through the catalytic layer to the hydrophobic diffusion layer without passing through the electrolyte due to its special structure, and constructs a superhydrophobic three-phase interface through the controllable preparation of its structure, thereby achieving efficient generation of H2O2.

[0010] In order to solve the above problems, the present invention provides a high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer, which forms a vertical array carbon nanocatalytic layer structure by using a controllable preparation method of its diameter, height and morphology, which has a shorter electron transmission path, high charge transfer efficiency and excellent gas diffusion capacity, and its high hydrophobicity is very important for maintaining a stable three-phase structure for a long time. The controllable preparation of the height of the vertical array carbon nanocatalytic layer helps to quickly transfer electrons from the catalyst to the collector, thereby preventing electron recombination. The controllable preparation of the morphology of the vertical array carbon nanocatalytic layer can increase the active sites of the electrolyte and promote ion transport. The layered and ordered support structure can accelerate the release of accumulated bubbles, especially in the electrowetting state, which helps to maintain the excellent performance of the electrode continuously and stably. The controllable preparation of the diameter size of the vertical array carbon nanocatalytic layer helps to form different pore sizes, and the ordered pore distribution is conducive to ion transport.

[0011] The high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer can be applied to an electrocatalytic device capable of achieving gas-liquid separation.

[0012] The principle of increasing the production of hydrogen peroxide is to achieve the best balance state of electrode gas-liquid. Generally speaking, the better the hydrophobicity of the electrode, the shorter the electron transmission path, the higher the charge transfer efficiency, the stronger the gas diffusion capacity, and the faster the rate of oxygen mass transfer, the better the performance of the electrode in producing hydrogen peroxide. The high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer used in the present invention has a special controllable vertical array structure. By regulating the different heights, diameters and morphologies of its structure, it can better construct a three-phase interface, thereby achieving the best state of electrode gas-liquid balance, achieving the ability to prevent the occurrence of electrowetting at high current density, and achieving the purpose of high yield and high utilization of hydrogen peroxide.

[0013] One object of the present invention is to disclose a high current carrying multiphase composite electrode with a vertical array carbon nanocatalyst layer, wherein a super hydrophobic vertical array carbon nanocatalyst layer is synthesized by a precursor carrier mechanism and a synchronous dual temperature zone, and a chemical vapor deposition method is used to assist the synthesis; the vertical array carbon nanocatalyst layer is negatively pressure thermally transferred onto the electrode to form a high current carrying multiphase electrode with a vertical array carbon nanocatalyst layer;

[0014] The synchronous dual temperature zones are a high temperature zone and a low temperature zone in a chemical vapor deposition furnace, the temperature of the low temperature zone is not less than 190°C, and the temperature of the high temperature zone is 850-950°C; the precursor is composed of a carbon source and a catalyst, and the mass ratio of the carbon source to the catalyst is 7.5-9:1; the catalyst is a metal catalyst with a particle size of 2nm-20nm; when preparing a vertical array carbon nanocatalytic layer, a precursor carrier is used to send the precursor to the low temperature zone, the precursor volatilizes instantly in the low temperature zone, and an inert gas is used as a carrier gas to bring the volatilized precursor from the low temperature zone to the high temperature zone. The carbon source is pyrolyzed on a quartz substrate under the action of the catalyst to begin to grow a vertical array carbon nanocatalytic material, and after continuing to grow at 850-950°C for 25-35 minutes, it is cooled to form a vertical array carbon nanocatalytic layer, wherein the flow rate of the inert gas is 400-600mL / min.

[0015] The precursor transport mechanism is used to transport the ark loaded with precursors to the low temperature zone, and retrieve the ark after the vertical array structure is prepared. The precursor transport mechanism can be a magnetron mechanism, such as the magnet and magnetron guide rail in the present invention, or any other mechanism that can realize the movement of the ark loaded with precursors.

[0016] The temperature of the low temperature zone is between the volatilization temperature of the carbon source and the carbonization temperature of the carbon source. The carbon source selected in the present invention has a low volatilization temperature of 170-190°C. When the precursor is pushed to the low temperature zone, it can be volatilized instantly, and then brought to the high temperature zone by the carrier gas and carbonized instantly after falling. If the volatilization speed is slow, it is difficult to quickly grow a vertical array morphology with the catalyst as the core.

[0017] The dual temperature zones mentioned in the present invention do not need to set a low-temperature program in the tube furnace, but only need to set a high-temperature program. When the high temperature reaches 900 degrees Celsius, if the infrared thermometer used to detect the temperature of the low-temperature zone shows that the temperature of the low-temperature zone has reached above 190°C, the ark containing the precursor is pushed along the magnetic control guide rail to a pre-marked temperature position, i.e., the low-temperature zone, through a magnet. The low-temperature zone and the high-temperature zone work at the same time to achieve successful preparation of the material.

[0018] The dual temperature zone has a significant effect on the growth morphology of the material. Because the instantaneous volatilization rate of the precursor is very important, the volatilization rate of the precursor determines the density of the catalyst deposited on the quartz substrate. The faster the precursor evaporates, the denser the carbon nanotubes grow on the quartz substrate. The mutual squeezing and dependence between the carbon nanotubes forces the carbon nanotubes to grow vertically and orderly. If the precursor is heated from room temperature to about 170-190°C at a certain rate, the volatilization rate of the precursor is slow, and the grown material will not have an obvious vertical array structure.

[0019] The dual temperature zones are closely related to the inert gas flow rate and can work synergistically with each other. The low temperature zone in the dual temperature zone is used for instant volatilization of the precursor, mainly to change the precursor from solid to liquid and finally to gas in a short period of time (about ten seconds). The role of the low temperature zone is to quickly change the state of the precursor in a short period of time, so that the precursor evaporates into gas and floats in the low temperature zone. The appropriate inert gas flow rate can drive the appropriate amount of gaseous precursor to flow to the quartz substrate in the high temperature zone to start growing a vertical array of carbon nanocatalytic layers.

[0020] The best position for the quartz substrate is in the middle of the furnace of the tube furnace. This is because the structure of the tube furnace causes the temperature inside to be convex. The temperature is highest near the center of the tube furnace (i.e., the set temperature is 900°C). As it moves away from the center of the tube furnace, the temperature near the inlet and outlet of the furnace gradually decreases. If it is lower than the set temperature, it is not conducive to the carbonization and volatilization growth of the material, and thus a vertical array structure with a suitable height will not be formed. In addition, the amount of precursor obtained in the middle of the tube furnace is also relatively appropriate, neither too much nor too little, and the amount of precursor can be fully utilized to grow a vertical array structure with a suitable height.

[0021] The closer the quartz substrate is to the precursor, the more carbon source and catalyst are obtained for growing the vertical array carbon nanocatalyst layer, and the height of the growth is too high. If the inert gas flow rate is too small, a large amount of carbon source and catalyst for growing the vertical array carbon nanocatalyst layer will accumulate in the tube furnace and will not be volatilized and taken away by the inert gas, which is not conducive to the formation of the vertical array carbon nanocatalyst layer.

[0022] The amount of carbon source and the stacking shape of carbon source in the furnace of the tube furnace will affect the morphology: the amount of carbon source is controlled at 350-390mg for the best growth of vertical array morphology structure. If the amount of carbon source is too much, that is, greater than 500mg, disordered carbon will appear on the array morphology formed, affecting the gas transmission performance of the final product. The stacking shape of the carbon source must be a trapezoidal shape, and it cannot be randomly stacked in a disorderly manner. The trapezoidal stacking structure is mainly to ensure that the amount of carbon source is less on the top and more on the bottom in this shape. The small amount on the upper layer is mainly to ensure that the carbon source is taken away by the inert gas before reaching the volatilization point, and the larger amount on the lower layer is mainly used to ensure that the carbon source is sufficient for the growth of the vertical array morphology.

[0023] The optimal ratio of carbon source to catalyst is 8.3:1. An inappropriate ratio of carbon source to catalyst will not grow a vertical array structure. If there is too much carbon source and insufficient catalyst, the catalytic performance of the material will be affected. If there is too much catalyst and insufficient carbon source, the material will not start to grow, and the carbon source will be exhausted, and the vertical array structure will not grow.

[0024] In the high current-carrying multiphase composite electrode, the carbon black and super-hydrophobic polymer composite layer is used as a carrier, and the nickel base is used as a multifunctional composite layer electrode of the current collector.

[0025] The preparation steps of the vertical array carbon nanocatalyst layer are as follows: the precursor evaporates instantly in the low temperature zone and is carried to the high temperature zone along with the inert gas, and then falls onto the quartz substrate; the position of the quartz substrate and the flow rate of the inert gas are adjusted to achieve the highly controllable growth of the vertical array carbon nanocatalyst layer; the size of the CoFeO2 nanoparticles is adjusted to achieve the diameter controllable growth of the vertical array carbon nanocatalyst layer, and the ratio of the carbon source and the catalyst is adjusted to achieve the morphology controllable growth of the vertical array carbon nanocatalyst layer.

[0026] Another object of the present invention is to provide a controllable preparation method of a high current-carrying multiphase composite electrode having a vertical array carbon nanocatalytic layer, comprising the following steps:

[0027] (1) Preparing a quartz substrate;

[0028] (2) The carbon source and the catalyst are mixed evenly in a mass ratio of 7.5-9:1 as a precursor for growing a vertical array carbon nanocatalytic layer; the carbon source and the catalyst are evenly mixed and stacked into a trapezoidal shape; the amount of the carbon source does not exceed 500 mg;

[0029] (3) placing a quartz substrate in the middle of a chemical vapor deposition furnace, which is a tubular furnace, and placing an ark containing the precursor on the air inlet side of the tubular furnace; introducing inert gas to exhaust the air in the quartz tube of the tubular furnace, and then heating the tubular furnace to 850-950°C after heating for 2-4 hours under the protection of the inert gas; the quartz substrate is 10-19 cm away from the precursor; the quartz substrate is 10-19 cm away from the precursor, which refers to the distance between the precursor and the quartz substrate when the magnet pushes the ark containing the precursor along the magnetron guide rail to the low-temperature zone on the left side of the tubular furnace; such a distance makes it convenient for the precursor to enter the low-temperature zone and evaporate instantly, and then reach the high-temperature zone in a very short time as the carrier gas moves and falls onto the quartz substrate to begin growing a vertical array of carbon nanocatalytic layers.

[0030] (4) When the temperature of the high temperature zone of the tube furnace reaches 850-950°C, the temperature of the low temperature zone of the tube furnace is not less than 190°C; the ark loaded with the precursor on the air inlet side of the tube furnace is pushed to the low temperature zone on the left side of the tube furnace along the magnetron guide rail by a magnet; the high temperature zone of 850-950°C in the middle of the tube furnace is used for the growth of the vertical array carbon nanocatalytic layer, and the low temperature zone on the left side of the air inlet of the tube furnace is used for the instantaneous volatilization of the precursor; the inert gas is used as a carrier gas to bring the instantaneous volatilized precursor from the low temperature zone to the high temperature zone and drop it onto the quartz substrate, and the carbon source begins to pyrolyze and grow a vertical array carbon nanocatalytic material under the action of the catalyst, and after continuing to grow at 850-950°C for 25-35 minutes, it is cooled under the protection of the inert gas to form a vertical array carbon nanocatalytic layer, wherein the flow rate of the inert gas ranges from 400 to 600 mL / min;

[0031] (5) negative pressure thermal transfer of the vertical array carbon nanocatalytic layer to the electrode to form a high current-carrying multiphase electrode with a vertical array carbon nanocatalytic layer; the specific thermal transfer process is: the quartz substrate with the vertical array carbon nanocatalytic layer and the electrode are operated under negative pressure, the negative pressure is -0.03 to -0.05 MPa, the transfer pressure is 3 to 5 MPa, the hot pressing temperature is 100 to 110°C, and the hot pressing time is 1 to 15 s; after the negative pressure hot pressing is completed, the pressure is adjusted to the standard atmospheric pressure and the quartz substrate is removed to achieve negative pressure thermal transfer of the vertical array carbon nanocatalytic layer.

[0032] Through negative pressure thermal transfer, the catalyst and the current collector can be hot-pressed to form a better bonding force, reduce the intermediate pores, increase the electron transfer rate and reduce the electrode impedance; negative pressure can allow Nafion to reach the surface of the array catalyst evenly, reducing the breakage rate during the thermal transfer process. The time of negative pressure transfer is 1 to 15 seconds. The transfer time is related to the thickness of the catalytic layer of the array electrode. When the thickness of the array carbon nanotube layer is 30 to 40um, the transfer time is controlled at 3 to 10s; when the thickness of the array carbon nanotube layer is 40 to 80um, the transfer time is controlled at 10 to 15s. When the transfer time is too long (for example, 5 minutes), the vertical array carbon nanocatalytic structure will be under pressure for a long time, causing damage to the catalytic structure.

[0033] The quartz substrate is 10-19cm away from the precursor. Since the precursor volatilizes instantly in the low temperature zone and is quickly brought to the high temperature zone by the carrier gas and grows on the quartz substrate, if the quartz substrate is too close to the precursor, the instantaneous carbon source accumulation is large, and disordered carbon is generated on the array structure, which is not conducive to the successful negative transfer of the array structure; if the quartz substrate is too far away from the precursor, the array structure formed is thin (that is, the height is too low), and the adhesion with the transfer substrate is poor, which is not conducive to the success of negative transfer. The quartz substrate is 10-19cm away from the precursor, so that the height of the array structure is appropriate, there is no formation of disordered carbon, and the adhesion with the transfer substrate is also good, and the transfer can be relatively complete and successful.

[0034] Preferably, the carbon source is a volatile carbon source such as camphor or sucrose. The mass ratio of the carbon source to the catalyst in step (2) is 8.3:1. The catalyst is a metal catalyst with a particle size of 2nm to 20nm; the metal catalyst is ferrocene or cobalt iron oxide. Preferably, the catalyst in step (2) can be CoFeO2 nanoparticles.

[0035] The preparation steps of CoFeO2 nanoparticle catalyst are as follows:

[0036] (1) a mixture of 6-7 mM Fe(acac)3, 3-4 mM Co(acac)2, 25-30 mM 1,2-hexadecanediol, 18-20 mM oleic acid and 18-20 mM oleylamine is mixed with a solvent, wherein acac represents acetylacetone;

[0037] (2) heating the mixture in a solvent from room temperature to 180-220° C. and stirring under inert gas protection; subsequently, stirring the obtained dark brown mixture at different reflux temperatures and continuously refluxing for different times, thereby obtaining CoFeO2 nanoparticles of different particle sizes;

[0038] The reflux temperature was set to 263-300°C, the heating rate was set to 4-14°C, and the reflux time was 30-70 min to prepare a CoFeO2 nanoparticle catalyst with a particle size of 2nm-20nm;

[0039] (3) After the reflux is completed, the mixture is cooled, the product is dissolved and centrifuged;

[0040] (4) Drying the precipitate, which is the catalyst.

[0041] The last object of the present invention is to disclose the application of the aforementioned high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer in improving the yield and current efficiency of in-situ electrocatalytic production of hydrogen peroxide or in cooperating with an ozone system to degrade pyridine. When used, due to its special vertical array structure, the height, diameter and morphology of the carbon nanocatalytic layer of the electrode can be controllably adjusted, thereby intuitively constructing a three-phase interface. Before catalyzing the synthesis of hydrogen peroxide in an electrocatalytic device, an electrode needs to be installed, wherein the high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer is used as a cathode; when hydrogen peroxide is produced, it is carried out in an electrocatalytic device; a ruthenium iridium titanium electrode (1.5cm×1.5cm) is installed in the electrocatalytic device as an anode, 100mL or 30mL of a 500mM Na2SO4 solution is prepared, the solution circulation flow rate is set to 50mL / min, the pressure control is selected to be 2.5-5KPa, the voltage is 4.35-5.02V, the current is 0.45A, the solution pH is adjusted to 7.0, and the reaction is carried out for 2h.

[0042] Preferably, the high current-carrying multiphase composite electrode is a sophisticated design of a self-modified dual-temperature zone magnetically controlled guide assisted CVD method. The precursor can be instantly volatilized at a specified temperature and then fall onto a quartz substrate. The position of the quartz substrate and the flow rate of the inert gas can be adjusted to achieve controllable growth (height, morphology, diameter) of the array carbon nanotubes.

[0043] In a preferred embodiment, the controllable preparation process of the high current carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer is:

[0044] (1) The size of the quartz substrate used (which is a quartz substrate plate) is 3 cm×3 cm×3 mm. Before synthesis, the quartz substrate needs to be cleaned with acetone or ethanol, then ultrasonically cleaned with pure water, and wiped smooth and bright with lens cleaning paper.

[0045] (2) The carbon source and the catalyst are mixed evenly in a certain mass ratio as a precursor for growing a vertical array carbon nanocatalytic layer. After the carbon source and the catalyst are mixed evenly, the stacking shape is a trapezoidal shape. They cannot be randomly stacked in a tubular furnace in a disorderly manner. The color is light yellow, and the precursor needs to be gently ground in a mortar. The amount of carbon source is optimally controlled between 350-390 mg and cannot exceed 500 mg. The optimal ratio (mass ratio) of carbon source and catalyst is 8.3:1.

[0046] (3) Place the quartz substrate in the middle of the tube furnace and place the ark containing the precursor on the air inlet side of the tube furnace. Inert gas is introduced to exhaust the air in the quartz tube in the tube furnace, and then the tube furnace is heated to 900°C after heating for 3 hours in an inert gas environment. The distance between the quartz substrate and the precursor can be set to 10-19 cm. The best choice is that the quartz substrate must be placed in the middle of the furnace of the tube furnace, which is conducive to the balanced growth of the vertical array structure and the successful negative transfer. The inert gases used in this process are argon, nitrogen, etc.

[0047] (4) When the temperature in the tube furnace reaches 900°C, immediately use a magnet to push the ark with the precursor on the air inlet side to the pre-marked position on the left side of the tube furnace - the low temperature zone (not less than 190°C). The high temperature zone of 900°C in the middle of the tube furnace is used for the growth of vertical array carbon nanostructures, and the low temperature zone on the left side of the tube furnace air inlet is used for the instantaneous volatilization of the precursor. At this time, the inert gas is used as a carrier gas to bring the instantaneous volatilized precursor from the low temperature zone to the high temperature zone, and it falls onto the quartz substrate. The carbon source begins to pyrolyze and grow a vertical array carbon nanostructure under the action of the catalyst. After continuing to grow at 900°C for 30 minutes, cool to room temperature in an inert gas environment. A vertical array carbon nanocatalytic layer can be formed, wherein the flow rate of the inert gas ranges from 400 to 600 mL / min. The optimal flow rate is 500 mL / min.

[0048] (5) The vertical array carbon nanocatalyst layer is transferred to a common electrode by a negative pressure thermal transfer machine to form a high current carrying multiphase electrode with a vertical array carbon nanocatalyst layer.

[0049] (6) Thermal transfer process: Place a small hot pressing mold, a quartz catalyst layer (i.e., a quartz substrate with a vertical array of carbon nanocatalytic layers) and an electrode under negative pressure, with a given negative pressure of -0.03 to -0.05 MPa, a transfer pressure of 3 to 5 MPa, a hot pressing temperature of 100 to 110°C, and a hot pressing time of 1 to 15 seconds. After the negative pressure hot pressing is completed, the pressure is adjusted to the standard atmospheric pressure and the quartz substrate is removed to achieve negative pressure thermal transfer of the catalyst layer.

[0050] Preferably, the carbon source in step (2) is mainly camphor, sucrose and other easily volatile materials. And the mass ratio of carbon source to catalyst is 7.5 to 9:1. The catalyst is a metal catalyst (ferrocene, cobalt iron oxide) with a particle size of 2nm to 20nm. If camphor is used as the carbon source, the state of the camphor needs to be observed before use. If the camphor particles are found to be relatively moist, they need to be placed in a vacuum dryer for drying.

[0051] In a preferred embodiment, the steps for preparing the CoFeO2 nanoparticle catalyst of different sizes in step (2) are as follows: (1) A mixture of 6-7 mM Fe(acac)3, 3-4 mM Co(acac)2, 25-30 mM 1,2-hexadecanediol, 18-20 mM oleic acid and 18-20 mM oleylamine is mixed with 60 mL of benzoyl ether or phenyl ether as a solvent. Wherein acac represents acetylacetone. (2) Under the flow of Ar gas, the mixture is heated from room temperature to 200°C in a benzoyl ether solvent and stirred for 2 h or stirred for 30 min in a phenyl ether solvent. Subsequently, the obtained dark brown mixture is stirred at different reflux temperatures and refluxed continuously for different times to obtain CoFeO2 nanoparticles of different sizes. (3) The reflux temperature of the water bath is set to 263-300°C, the heating rate is set to 4-14°C, the reflux time is 30-70 min, and the mixture is immersed in a solvent (60 mL of phenyl ether or benzoyl ether) to prepare a 2nm-20nm CoFeO2 nanoparticle catalyst. (4) After the reflux is completed, the product is cooled to room temperature and mixed in 40 mL of anhydrous ethanol. Then, the mixture is separated and placed in four centrifuge tubes and centrifuged at 9000-10000 rpm for 8-10 min. After removing the supernatant, the precipitate is mixed in 30 mL of ethanol. Then, the mixture is placed in two centrifuge tubes and centrifuged for 5-10 min. Repeat this operation twice. (5) After removing the supernatant, the precipitate is heated and dried at 50-60°C for 12-15 h. Then, a black precipitate is obtained. This black precipitate is the catalyst.

[0052] In a preferred embodiment, if the size of CoFeO2 nanoparticles needs to be precisely controlled, the reflux temperature of the water bath needs to be set to 265°C, the heating rate is 5°C, the reflux time is 32min, the immersion solvent is 60ml of phenyl ether, and 2-4nm CoFeO2 nanoparticle catalysts are prepared. The reflux temperature of the water bath is set to 275°C, the heating rate is 8°C, the reflux time is 58min, the immersion solvent is 60ml of benzoyl ether, and 6-10nm CoFeO2 nanoparticles are prepared. The reflux temperature of the water bath is set to 298°C, the heating rate is 12°C, the reflux time is 66min, the immersion solvent is 60ml of benzoyl ether, and 13-20nm CoFeO2 nanoparticles are prepared. CoFeO2 nanoparticles are made by three steps of hydrothermal + centrifugation + drying, which can effectively remove impurities in the catalyst and improve the purity of the catalyst.

[0053] In a preferred embodiment, the diameter size control synthesis of the high current carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer requires the use of an electric mass flowmeter to control the flow of Ar, Ar+H2 (4%) and acetylene (C2H2). Under the Ar+H2 or C2H2 flow state, the pressure is set to 103KPa. At 1023K, a gas ventilation state is performed under the Ar+H2 flow for 60 minutes. Then, stay under the C2H2 flow at 1023K (750°C) for 10 minutes to grow a vertical array carbon nanocatalytic layer.

[0054] Preferably, the hot-press transfer in step (5) requires the configuration of a certain transfer liquid, wherein the transfer liquid is 1 mL of isopropanol and 50 microliters of 5 wt% Nafion solution, and ultrasonication is performed for 5 minutes.

[0055] The high current-carrying multiphase composite electrode with a vertical array of carbon nanocatalytic layers is cut into electrode products of the same size after being manufactured. The effective area of ​​the electrode product is 2cm 2 .

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] The present invention relates to the controllable preparation and application of the diameter, height and morphology of a high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer, which is applied to the in-situ electrochemical production of hydrogen peroxide under industrial-grade high current or the degradation of pyridine in a coordinated ozone system.

[0058] The present invention forms a dual-temperature zone by a magnetically controlled guide rail assisted method and adopts a CVD method to synthesize a vertical array carbon nano-catalytic layer of different structural sizes, mainly adjusting the diameter and height of the carbon nanotubes of the vertical array structure to enhance the electrode current carrying and electrocatalytic performance, and to prepare an electrode with high current carrying and high catalytic efficiency performance. This electrode comprises a super-hydrophobic vertical array carbon nano-structure layer as a catalytic layer, a carbon black and super-hydrophobic polymer composite layer as a carrier, and a nickel base as a current collector. Compared with the traditional disordered multiphase electrode, the high current carrying multiphase electrode of the present invention can be achieved at industrial-grade large currents (300mA / cm 2 ) maintains high current efficiency under high current density. The composite electrode is mainly used for in-situ electrocatalytic production of hydrogen peroxide. Under high current density conditions, its hydrogen peroxide concentration can reach 1-5wt%, and the current efficiency can be maintained at 80-99%.

[0059] The high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer prepared by the present invention can controllably adjust the height, diameter and morphology of the carbon nanocatalytic layer structure, thereby better constructing the three-phase interface of the electrode, optimizing various properties of the electrode, and significantly improving the performance of the electrode in producing hydrogen peroxide, so that the electrode can be operated and used under industrial-grade high currents. The preparation method is novel, the electrode has good stability, and is suitable for large-scale industrial production.

[0060] The high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer of the present invention has good stability and can maintain a relatively high hydrogen peroxide production during long-term operation, while also being able to efficiently degrade the difficult-to-degrade substance - pyridine. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 The electron microscope image of the high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer prepared by the present invention;

[0062] Figure 2 The yield of hydrogen peroxide obtained in Example 3 and its corresponding current efficiency diagram, a, yield; b, current efficiency;

[0063] Figure 3 The graph is a graph of the yield of hydrogen peroxide and its corresponding current efficiency obtained in Example 4;

[0064] Figure 4 The yield of hydrogen peroxide obtained in Example 5 and its corresponding current efficiency diagram;

[0065] Figure 5 A long-term production diagram of a high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer prepared by the present invention;

[0066] Figure 6 Schematic diagram of using a high current-carrying multiphase composite electrode with a vertically arrayed carbon nanocatalytic layer to collaborate with an ozone system to degrade pyridine, a difficult-to-degrade substance.

[0067] Figure 7 It is a schematic diagram of the structure of each component of the tube furnace;

[0068] Among them, 1 is air inlet, 2 is air outlet, 3 is magnet, 4 is ark, 5 is magnetic control guide rail, 6 is low temperature zone, 7 is high temperature zone, 8 is furnace, 9 is tubular furnace, 10 is quartz substrate, 11 is quartz tube, and 12 is magnetic control point. DETAILED DESCRIPTION

[0069] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0070] In a specific embodiment, three different electrodes were prepared to compare their performance in electrogenerating hydrogen peroxide. The three electrodes were named as ordinary hot-pressed electrode, disordered electrode, and high current-carrying multiphase composite electrode with vertical array carbon nanocatalytic layer (abbreviated as: carbon array catalytic layer composite electrode).

[0071] When preparing a high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer, the present invention adopts an improved CVD tube furnace. The improved CVD tube furnace 9 includes an air inlet 1, an air outlet 2, a furnace chamber 8, and a quartz tube 11, all of which are prior arts. The magnet 3 and the magnetron guide rail 5 are located on the air inlet side, the magnet is located inside the quartz tube of the tube furnace and is not located in the furnace chamber, while the magnetron guide rail is located outside the quartz tube of the tube furnace, and the magnet can push the ark loaded with the precursor to move along the magnetron guide rail, so that the ark 4 loaded with the precursor enters the low temperature zone on the left side of the tube furnace (i.e., the left side of the quartz tube), and the low temperature zone is located inside the quartz tube, and the low temperature zone 6 is Figure 7 The dotted line in the quartz tube. High temperature zone 7 is Figure 7 The quartz substrate 10 in the quartz tube and above the quartz substrate. The magnetron guide is fixed, and a movable magnetic control point 12 (a small magnet) is set in the magnetron guide. The magnetic control point 12 and the magnet 3 are opposite and attracted to each other. The magnetic control point 12 is moved to drive the magnet 3 to move along the magnetron guide, and the ark loaded with the precursor is located in front of the magnet 3, so that the ark loaded with the precursor is pushed to the low temperature area by the magnet 3; then, the magnetic control point 12 is returned to drive the magnet 3 to return to the original position to prevent the magnet from staying in the low temperature area and causing demagnetization.

[0072] The performance of the high current-carrying composite electrode with a vertical array carbon nano-catalytic layer prepared by the present invention is tested by using an electrocatalytic device, in which a ruthenium-iridium-titanium electrode (1.5 cm×1.5 cm) is installed as an anode, and a common hot-pressed electrode, a disordered electrode or a high current-carrying multiphase composite electrode with a vertical array carbon nano-catalytic layer is used as a cathode. Among them, a high current-carrying multiphase composite electrode with a vertical array carbon nano-catalytic layer is mainly used as a cathode. In addition, the electrocatalytic device is subjected to certain condition setting optimization treatment to improve the performance of the high current-carrying composite electrode with a vertical array carbon nano-catalytic layer in the electrocatalytic production of hydrogen peroxide.

[0073] Example 1

[0074] The specific preparation process of the high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer of this embodiment is as follows:

[0075] Prepare a quartz substrate: 3cm×3cm×3mm. The quartz substrate needs to be cleaned with ethanol first, then ultrasonically cleaned with pure water, and wiped smooth with lens paper. Sucrose and CoFeO2 catalyst are mixed evenly in a mass ratio of 8.3:1 as a precursor for growing a vertical array carbon nanocatalytic layer; sucrose and catalyst are evenly mixed and stacked into a trapezoidal shape; the amount of sucrose is 360mg; the preparation process of CoFeO2 catalyst: a mixture of 6.5mM Fe(acac)3, 3.5mM Co(acac)2, 28mM 1,2-hexadecanediol, 20mM oleic acid and 20mM oleylamine is mixed with as a solvent 60mL of benzoyl ether; wherein acac represents acetylacetone; under the flow of Ar gas, the mixture is heated from room temperature to 200°C in a benzoyl ether solvent and stirred for 2h; then, the obtained dark brown mixture is stirred at reflux temperature and refluxed continuously for a certain time to obtain CoFeO2 nanoparticles; the reflux temperature of the water bath is set to 298°C, the heating rate is: 12°C, the reflux time is 66min, the immersion solvent is: 60ml benzoyl ether, and 13-20nm CoFeO2 nanoparticles are prepared; after the reflux is completed, the product is cooled to room temperature and mixed in 40mL of anhydrous ethanol; then, the mixture is separated and placed in four centrifuge tubes and centrifuged at 9000rpm for 10min; after removing the supernatant, the precipitate is mixed in 30mL of ethanol; then, the mixture is placed in two centrifuge tubes and centrifuged for 5min; repeat this operation twice; after removing the supernatant, the precipitate is heated and dried at 55°C for 12h; then, a black precipitate is obtained; this black precipitate is the catalyst.

[0076] Place the quartz substrate in the middle of a chemical vapor deposition furnace, which is a CVD tube furnace, and place the ark containing the precursor on the air inlet side of the tube furnace; introduce Ar to exhaust the air in the quartz tube of the tube furnace, and then heat the tube furnace to 900°C after heating for 3 hours under Ar protection; the quartz substrate is 15 cm away from the precursor; when the temperature in the high temperature zone of the tube furnace reaches 900°C, the temperature in the low temperature zone of the tube furnace is not less than 190°C; use a magnet to push the ark containing the precursor on the air inlet side of the tube furnace along the magnetron guide rail to the low temperature zone on the left side of the tube furnace; The high temperature zone of 900°C in the middle of the tube furnace is used for the growth of the vertical array carbon nanocatalytic layer, and the low temperature zone on the left side of the air inlet of the tube furnace is used for the instantaneous volatilization of the precursor; Ar is used as a carrier gas to bring the instantaneous volatilized precursor from the low temperature zone to the high temperature zone and drop it onto the quartz substrate. The carbon source begins to pyrolyze and grow a vertical array carbon nanocatalytic material under the action of the catalyst. After continuous growth at 900°C for 30 minutes, it is cooled under the protection of Ar to form a vertical array carbon nanocatalytic layer, wherein the flow rate of Ar is in the range of 500mL / min.

[0077] The vertical array carbon nanocatalytic layer is negatively pressure-thermally transferred to the common hot-pressed electrode to form a high current-carrying multiphase electrode with a vertical array carbon nanocatalytic layer; the specific thermal transfer process is: the quartz substrate with the vertical array carbon nanocatalytic layer and the common hot-pressed electrode prepared in Example 3 are operated under negative pressure, the negative pressure is -0.04Mpa, the transfer pressure is 4MPa, the hot-pressing temperature is 100°C, and the hot-pressing time is 8s; after the negative pressure hot-pressing is completed, the pressure is adjusted to the standard atmospheric pressure and the quartz substrate is removed, and the vertical array carbon nanocatalytic layer is successfully transferred to the common hot-pressed electrode. After the transfer, the vertical array carbon nanocatalytic layer is in close contact with the catalyst ink layer of the common hot-pressed electrode.

[0078] Figure 1 This is an electron microscope image of a high-current-carrying multiphase composite electrode with a vertical array type carbon nano-catalyst layer prepared in Example 1; the left image is a vertical array structure catalyst layer grown on a quartz substrate, from which it can be seen that the vertical array structure has been successfully formed; the right image is a schematic structural diagram of a high-current-carrying multiphase composite electrode with a vertical array type carbon nano-catalyst layer, from which it can be seen that negative pressure thermal transfer of the vertical array type carbon nano-catalyst layer has been achieved.

[0079] Example 2

[0080] The specific preparation process of the high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer of this embodiment is as follows:

[0081] Prepare a quartz substrate: 3cm×3cm×3mm. The quartz substrate needs to be cleaned with ethanol first, then ultrasonically cleaned with pure water, and wiped smooth and bright with lens paper. By adding different amounts of camphor and ferrocene (ferrocene particle size 14-16nm, purity is 98%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., molecular formula is C 10 H 10 Fe), so that the ratio (mass ratio) is Cp:Fe=12.5:1, Cp:Fe=10.7:1, Cp:Fe=8.3:1, Cp:Fe=7.5:1, and they are mixed evenly as a precursor for growing a vertical array carbon nanocatalytic layer; camphor and ferrocene are mixed evenly and stacked into a trapezoidal shape; the amount of camphor is 360 mg;

[0082] Place the quartz substrate in the middle of a chemical vapor deposition furnace, which is a CVD tube furnace, and place the ark containing the precursor on the air inlet side of the tube furnace; introduce Ar to exhaust the air in the quartz tube of the tube furnace, and then heat the tube furnace to 900°C after heating for 3 hours under Ar protection; the quartz substrate is 15 cm away from the precursor; when the temperature in the high temperature zone of the tube furnace reaches 900°C, the temperature in the low temperature zone of the tube furnace is not less than 190°C; use a magnet to push the ark containing the precursor on the air inlet side of the tube furnace along the magnetron guide rail to the low temperature zone on the left side of the tube furnace; The high temperature zone of 900°C in the middle of the tube furnace is used for the growth of the vertical array carbon nanocatalytic layer, and the low temperature zone on the left side of the air inlet of the tube furnace is used for the instantaneous volatilization of the precursor; Ar is used as a carrier gas to bring the instantaneous volatilized precursor from the low temperature zone to the high temperature zone and drop it onto the quartz substrate. The carbon source begins to pyrolyze and grow a vertical array carbon nanocatalytic material under the action of the catalyst. After continuous growth at 900°C for 30 minutes, it is cooled under the protection of Ar to form a vertical array carbon nanocatalytic layer, wherein the flow rate of Ar is in the range of 500mL / min.

[0083] The vertical array carbon nanocatalyst layer is negatively pressure thermally transferred to an ordinary hot pressing electrode to form a high current-carrying multiphase electrode with a vertical array carbon nanocatalyst layer; the thermal transfer process is specifically as follows: the quartz substrate with the vertical array carbon nanocatalyst layer and the ordinary hot pressing electrode prepared in Example 3 are operated under negative pressure, the negative pressure is -0.04Mpa, the transfer pressure is 4MPa, the hot pressing temperature is 100°C, and the hot pressing time is 8s; after completing the negative pressure hot pressing, the pressure is adjusted to the standard atmospheric pressure and the quartz substrate is removed to achieve negative pressure thermal transfer of the vertical array carbon nanocatalyst layer.

[0084] Example 3

[0085] This embodiment mainly uses a high current carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer, a common hot pressing electrode, and a disordered electrode. Three different electrodes are used at 10-350mA / cm 2The performance of electrogenerated hydrogen peroxide was investigated at a current density of . Take 1g of acidified carbon black (CABOTVXC-72 conductive carbon black), 26mL of 95% ethanol solution, 1.2mL of 60wt% polytetrafluoroethylene concentrated dispersion, wherein the acidified carbon black is used as a catalyst and the 60wt% polytetrafluoroethylene concentrated dispersion is used as a gelling agent, stir for 12min, ultrasonicate for 35min, and then dry into a semi-solid at 65°C; roll the semi-solid (catalyst ink) into a spherical shape, place it on the nickel mesh for standby use, put it into the hot press pressing platform, adjust the appropriate temperature and hot pressing pressure, the hot pressing temperature is 60°C, the hot pressing pressure is 15MPa, and the pressing time is 20s to make a carbon black gas diffusion electrode, referred to as a common hot pressing electrode. Take 10 mg of commercially purchased disordered carbon nanotubes, take 2 mL of ethanol solution, and 100 μL of 5 wt% Nafion solution, mix them evenly, and then ultrasonicate for 30 minutes. After oscillation 3 times, use a spin coater or a small spray gun to load them on the carbon black gas diffusion electrode prepared above, referred to as the disordered electrode.

[0086] The high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer of this embodiment is prepared by Example 1.

[0087] Anode: cation exchange membrane (Nafion115 membrane), ruthenium-iridium-titanium electrode (titanium-based, ruthenium-iridium-plated electrode, size 1.5cm×1.5cm) with 0.5M-30mL sulfuric acid solution, the circulation flow rate is 5mL / min, cathode: high current carrying multiphase composite electrode with vertical array carbon nanocatalytic layer, ordinary hot pressing electrode or disordered electrode (1.5cm×1.5cm). The current range is 0.022-0.787A, the voltage range is between 1.71-5.86V, and the oxygen pressure control condition is: when the current density is 10-100mA / cm 2 When the oxygen pressure is controlled at 2.5KPa, the current density is 150mA / cm 2 When the oxygen pressure is controlled at 3.5KPa, the current density is 200-350mA / cm 2 , and the oxygen pressure is controlled at 4.5KPa. The effect of adding 0.5M-30mL Na2SO4 solution as electrolyte, with a circulation flow rate of 50mL / min and an electrode spacing (i.e., the spacing between cathode and anode) of 3mm on the H2O2 yield and current efficiency when running for 2h.

[0088] like Figure 2 The high current carrying multiphase composite electrode with vertical array carbon nanocatalytic layer (referred to as carbon array catalytic layer composite electrode) has the best performance of electrogenerating hydrogen peroxide, 200mA / cm 2 The current density is the best, 350mA / cm 2The current density is the limiting current density of the carbon array catalytic layer composite electrode. When the applied current density is low, the current efficiency can be as high as 99%. As the current density increases, the current efficiency decreases, and the H2O2 yield of the carbon array catalytic layer composite electrode increases first and then decreases. The current density is 250mA / cm 2 or 300mA / cm 2 When the H2O2 yield is as high as 164 mg h -1 cm -2 When the current density is 250mA / cm 2 , its current efficiency is about 90%, and the current density is 300mA / cm 2 When the current density is 200mA / cm 2 The maximum H2O2 yield can reach 138 mg h -1 cm -2 When the current density reaches 350mA / cm 2 When the yield decreases, the current efficiency also decreases significantly, only about 50%, indicating that this has reached the limiting current density of the carbon array catalytic layer composite electrode.

[0089] Example 4

[0090] This embodiment mainly uses a high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer doped with different amounts of catalyst and carbon source ratios (using the preparation process of Example 2) to explore the performance of electrogenerated hydrogen peroxide, and ordinary hot pressing electrodes and disordered electrodes are used as controls. The vertical array carbon nanocatalytic layer of different structural sizes is synthesized by CVD method by forming a dual temperature zone through a magnetic control guide assisted method, and the diameter and height of the carbon nanotubes of the vertical array structure are mainly adjusted to enhance the electrode current carrying and electrocatalytic performance, and a high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer having high current carrying and high catalytic efficiency performance is prepared. By adding different amounts of camphor and ferrocene, the ratio is Cp:Fe=12.5:1, Cp:Fe=10.7:1, Cp:Fe=8.3:1, Cp:Fe=7.5:1. Cp is the abbreviation for camphor, and Fe is the abbreviation for ferrocene. Anode: cation exchange membrane (Nafion115 membrane), ruthenium-iridium-titanium electrode (titanium-based, ruthenium-iridium-plated electrode, size 1.5cm×1.5cm) with 0.5M-30mL sulfuric acid solution, the circulation flow rate is 5mL / min, cathode: high current carrying multiphase composite electrode with vertical array carbon nanocatalytic layer (1.5cm×1.5cm). Oxygen pressure control condition is 4.5KPa. Current density: 200mA / cm 2The current is 0.45A and the voltage is 4.16V. The effect of adding 0.5M-100mL Na2SO4 solution as electrolyte, with a circulation flow rate of 50mL / min and an electrode spacing of 10mm, on the H2O2 yield and current efficiency when running for 2h.

[0091] like Figure 3 As shown, when Cp:Fe=8.3:1, the performance of the high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer to produce hydrogen peroxide is the best. When Cp:Fe=8.3:1, the yield of H2O2 is significantly improved, and its yield is 137 mgh -1 cm -2 The current efficiency is about 95%, which has achieved unexpected technical results. However, the performance of the high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer for producing hydrogen peroxide is obviously low for the other doping ratios, so it can be judged that the other doping ratios are not appropriate.

[0092] Example 5

[0093] This embodiment mainly uses a high-current multiphase composite electrode with a vertical array carbon nanocatalytic layer to explore the performance of electrogenerated hydrogen peroxide at different Ar flow rates, and ordinary hot pressing electrodes and disordered electrodes are used as controls. In this embodiment, the preparation process of the high-current multiphase composite electrode with a vertical array carbon nanocatalytic layer is the same as that of Example 1 except that the Ar flow rate is changed. The vertical array carbon nanocatalytic layer of different structural sizes is synthesized by CVD method by forming a dual temperature zone through a magnetically controlled guide rail assisted method, and the diameter and height of the carbon nanotubes of the vertical array structure are mainly adjusted to enhance the electrode current carrying and electrocatalytic performance, and to prepare a multiphase carbon-based composite electrode with high current carrying and high catalytic efficiency performance, that is, a high-current multiphase composite electrode with a vertical array carbon nanocatalytic layer. By adjusting different Ar flow rates, for example, adjusting the Ar flow rate of the tubular furnace to 400mL / min, 450mL / min, 500mL / min, 550mL / min, and 600mL / min. Anode: cation exchange membrane (Nafion115 membrane), ruthenium-iridium-titanium electrode (titanium-based, ruthenium-iridium-plated electrode, size 1.5cm×1.5cm) with 0.5M-30mL sulfuric acid solution, the circulation flow rate is 5mL / min, cathode: high current carrying multiphase composite electrode with vertical array carbon nanocatalytic layer (1.5cm×1.5cm). Oxygen pressure control condition is 4.5KPa. Current density: 200mA / cm 2The current is 0.45A and the voltage is 4.32V. The effect of adding 0.5M-100mL Na2SO4 solution as electrolyte, with a circulation flow rate of 50mL / min and an electrode spacing of 10mm, on the H2O2 yield and current efficiency when running for 2h.

[0094] like Figure 4 As shown in the figure, when the Ar flow rate is 500 mL / min, the performance of the carbon array catalytic layer composite electrode in producing hydrogen peroxide is the best. When the Ar flow rate is 500 mL / min, H2O2 is continuously and stably produced in the system with a yield of 136 mg h -1 cm -2 The current efficiency is about 94.5%. For other Ar flow rates, the performance of the carbon array catalytic layer composite electrode made of the grown carbon nanoarray structure to produce hydrogen peroxide is obviously low, so it can be judged that the other Ar flow rates are not appropriate.

[0095] Application Example 1

[0096] This application example mainly uses the high current-carrying multiphase composite electrode with a vertical array carbon nano-catalytic layer of Example 1 to explore the electrogenerated hydrogen peroxide production under long-term operation. Anode: a cation exchange membrane (Nafion115 membrane), a ruthenium-iridium-titanium electrode (an electrode with a titanium substrate and ruthenium-iridium plating, with a size of 1.5cm×1.5cm) passes through 0.5M-30mL of sulfuric acid solution, and its circulation flow rate is 5mL / min, cathode: a high current-carrying multiphase composite electrode with a vertical array carbon nano-catalytic layer (1.5cm×1.5cm). The oxygen pressure control condition is 4.5KPa. Current density: 200mA / cm 2 The current is 0.45A and the voltage is 4.22V. The effect of adding 0.5M-100mL Na2SO4 solution as electrolyte, with a circulation flow rate of 50mL / min and an electrode spacing of 10mm, on the H2O2 yield and current efficiency when running for 10h.

[0097] like Figure 5 As shown in the figure, after 10 hours of reaction at high current density, the high current carrying multiphase composite electrode with vertical array carbon nanocatalytic layer reaches the highest concentration, i.e., about 3.5wt%, and the current efficiency is about 40%. This is because the environment for electrogenerated H2O2 gradually changes from neutral to acidic. The pH value detected at 6 hours is 3.15, at 8 hours is 2.17, and at 10 hours is 2.05. As the reaction time increases, the overly acidic environment is not conducive to the production and testing of hydrogen peroxide, and the concentration of H2O2 gradually reaches a state of equilibrium, so the current efficiency decreases. At 200mA / cm 2The high current density of 10 h indicates that the high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer has excellent performance in the electroproduction of hydrogen peroxide, providing a theoretical basis for the industrial use of high current electroproduction of hydrogen peroxide.

[0098] Application Example 2

[0099] This application example mainly uses the electrocatalytic system of producing hydrogen peroxide with a high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer in Example 1 in conjunction with the ozone system, and can also degrade pyridine substances. This is because the electroperoxidation technology E-Peroxone can generate H2O2 in situ on the cathode, which then stimulates the generation of reactive oxygen species ROS. The removal of pyridine comes from the two reactions of O3 and ·OH generated by O3 / H2O2. Configuration 400mL 100mg L -1 Pyridine solution and 250 mL 50 mM Na2SO4 solution, then add 5 mM tert-butyl alcohol (TBA) and 5 mM chloroform (CHCl3) as ·OH and O 2- Inhibitor of free radicals, measuring the removal effect of pyridine. Anode: cation exchange membrane (Nafion115 membrane), ruthenium-iridium-titanium electrode (titanium-based, ruthenium-iridium-plated electrode, size 1.5cm×1.5cm) passes 0.5M-30mL sulfuric acid solution, the circulation flow rate is 5mL / min, cathode: high current-carrying multiphase composite electrode with vertical array carbon nanocatalytic layer (1.5cm×1.5cm). Oxygen pressure control condition is 4.5KPa. Current density: 200mA / cm 2 . The current is 0.45A and the voltage is 4.46V. The effect of adding 0.5M-100mL Na2SO4 solution as electrolyte, with a circulation flow rate of 50mL / min and an electrode spacing of 10mm, on the removal rate of pyridine when running for 15 minutes. However, the unimproved electrode (ordinary hot-pressed electrode or disordered electrode, also used as cathode) produces a small amount of hydrogen peroxide and a limited number of ·OH produced during the reaction, so the removal rate of pyridine within 15 minutes can only reach 65%, and the pyridine substance cannot be completely degraded. However, the high current-carrying multi-phase composite electrode with a vertical array carbon nanocatalytic layer of the present invention has a pyridine removal rate of nearly 100% within 15 minutes, such as Figure 6 shown.

[0100] The present invention specifically relates to the preparation and application of a high current carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer. The preparation method is novel and only one furnace is needed to realize dual temperature zone control. The method mainly utilizes a magnetic control guide rail to form a low temperature zone and a high temperature zone, and a vertical array carbon nanocatalytic layer with controllable diameter, height and morphology can be grown by chemical vapor deposition. This special structure is used to form a three-phase interface, thereby achieving the best state of gas-liquid equilibrium, preventing the electrode surface from being flooded with water by electrowetting at high current density, thereby affecting the performance of the electrode in producing hydrogen peroxide.

[0101] Due to the ingenious design of the self-modified dual-temperature zone magnetic control rail assisted CVD method adopted in the present invention, the precursor can fall on the quartz substrate after instant volatilization at a specified temperature, and the height of the vertical array carbon nano catalyst layer can be controlled by adjusting the position of the quartz substrate and the size of the gas flow rate, and the diameter of the vertical array carbon nano catalyst layer can be controlled by adjusting the size of the CoFeO2 nanoparticles, and the morphology of the vertical array carbon nano catalyst layer can be controlled by adjusting the ratio of the carbon source and the catalyst. The super-hydrophobic vertical array carbon nano structure layer is used as a catalyst layer, carbon black and super-hydrophobic polymer composite layer are used as carriers, and the nickel base is used as a multifunctional composite structure of the current collector, which improves the stability of the electrode, prolongs the service life of the electrode, and can efficiently produce hydrogen peroxide in situ. Considering the formation of this special structure of the vertical array, the specific carbon source and the doping ratio of the catalyst and the Ar flow rate of the high current-carrying multiphase composite electrode with a vertical array carbon nano catalyst layer in the present invention have a great influence on the yield and current efficiency of the final in-situ electrocatalytic production of hydrogen peroxide.

[0102] The high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer prepared by the present invention can controllably adjust the height, diameter and morphology of the carbon nanocatalytic layer structure, thereby better constructing the three-phase interface of the electrode, optimizing various properties of the electrode, and significantly improving the performance of the electrode in producing hydrogen peroxide, so that the electrode can be operated and used under industrial-grade high currents. The preparation method is novel, the electrode has good stability, and is suitable for large-scale industrial production.

[0103] The high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer of the present invention has good stability and can maintain a relatively high hydrogen peroxide production during long-term operation, while also being able to efficiently degrade the difficult-to-degrade substance - pyridine.

[0104] The present invention realizes efficient in-situ production of hydrogen peroxide. The hydrogen peroxide output can reach 1-5wt% at high current density, and the yield can reach 137mg h -1 cm -2 The current efficiency is about 95%, while the yield of the unmodified electrode (i.e., the ordinary hot-pressed electrode and the disordered electrode in Example 1) is 70 mg h-1 cm -2 , the current efficiency is 40%, indicating that the performance of its electrogenerated hydrogen peroxide decreases significantly at high current density.

[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high current carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer, characterized in that: A super-hydrophobic vertical array carbon nanocatalyst layer is synthesized by assisted chemical vapor deposition through a precursor carrier mechanism and synchronous dual temperature zones; the vertical array carbon nanocatalyst layer is negatively pressure thermally transferred onto an electrode to form a high current-carrying multiphase electrode having a vertical array carbon nanocatalyst layer; The synchronous dual temperature zones are the high temperature zone and the low temperature zone in the chemical vapor deposition furnace, the temperature of the low temperature zone is not less than 190°C, and the temperature of the high temperature zone is 850-950°C; the precursor is composed of a carbon source and a catalyst, and the mass ratio of the carbon source to the catalyst is 7.5-9:1; the catalyst is a metal catalyst with a particle size of 2nm-20nm; when preparing a vertical array carbon nanocatalytic layer, the precursor carrier is used to send the precursor to the low temperature zone, the precursor volatilizes instantly in the low temperature zone, and the inert gas is used as a carrier gas to bring the volatilized precursor from the low temperature zone to the high temperature zone. The carbon source is pyrolyzed on the quartz substrate under the action of the catalyst to begin to grow a vertical array carbon nanocatalytic material. After continuing to grow at 850-950°C for 25-35 minutes, it is cooled to form a vertical array carbon nanocatalytic layer, wherein the flow rate of the inert gas is 400-600mL / min.

2. A high current carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer as claimed in claim 1, characterized in that: In the high current-carrying multiphase composite electrode, the carbon black and super-hydrophobic polymer composite layer is used as a carrier, and the nickel base is used as a multifunctional composite layer electrode of the current collector.

3. The high current carrying multi-phase composite electrode with a vertical array carbon nanocatalytic layer as claimed in claim 1, characterized in that: The preparation steps of the vertical array carbon nanocatalyst layer are as follows: the precursor evaporates instantly in the low temperature zone and is carried to the high temperature zone along with the inert gas, and then falls onto the quartz substrate; the position of the quartz substrate and the flow rate of the inert gas are adjusted to achieve the highly controllable growth of the vertical array carbon nanocatalyst layer; the size of the CoFeO2 nanoparticles is adjusted to achieve the diameter controllable growth of the vertical array carbon nanocatalyst layer, and the ratio of the carbon source and the catalyst is adjusted to achieve the morphology controllable growth of the vertical array carbon nanocatalyst layer.

4. The controllable preparation method of a high current-carrying multiphase composite electrode having a vertical array carbon nanocatalytic layer according to any one of claims 1 to 3, characterized in that: The steps include: (1) Preparing a quartz substrate; (2) The carbon source and the catalyst are mixed evenly in a mass ratio of 7.5-9:1 as a precursor for growing a vertical array carbon nanocatalytic layer; the carbon source and the catalyst are evenly mixed and stacked into a trapezoidal shape; the amount of the carbon source does not exceed 500 mg; (3) placing a quartz substrate in the middle of a chemical vapor deposition furnace, which is a tubular furnace, and placing an ark containing a precursor on the air inlet side of the tubular furnace; introducing an inert gas to exhaust the air in the quartz tube of the tubular furnace, and then heating the tubular furnace to 850-950°C after heating for 2-4 hours under the protection of the inert gas; the quartz substrate is 10-19 cm away from the precursor; (4) When the temperature of the high temperature zone of the tube furnace reaches 850-950°C, the temperature of the low temperature zone of the tube furnace is not less than 190°C; the ark loaded with the precursor on the air inlet side of the tube furnace is pushed to the low temperature zone on the left side of the tube furnace along the magnetron guide rail by a magnet; the high temperature zone of 850-950°C in the middle of the tube furnace is used for the growth of the vertical array carbon nanocatalytic layer, and the low temperature zone on the left side of the air inlet of the tube furnace is used for the instantaneous volatilization of the precursor; the inert gas is used as a carrier gas to bring the instantaneous volatilized precursor from the low temperature zone to the high temperature zone and drop it onto the quartz substrate, and the carbon source begins to pyrolyze and grow a vertical array carbon nanocatalytic material under the action of the catalyst, and after continuing to grow at 850-950°C for 25-35 minutes, it is cooled under the protection of the inert gas to form a vertical array carbon nanocatalytic layer, wherein the flow rate of the inert gas ranges from 400 to 600 mL / min; (5) negative pressure thermal transfer of the vertical array carbon nanocatalytic layer to the electrode to form a high current-carrying multiphase electrode with a vertical array carbon nanocatalytic layer; the specific thermal transfer process is: the quartz substrate with the vertical array carbon nanocatalytic layer and the electrode are operated under negative pressure, the negative pressure is -0.03 to -0.05 MPa, the transfer pressure is 3 to 5 MPa, the hot pressing temperature is 100 to 110°C, and the hot pressing time is 1 to 15 s; after the negative pressure hot pressing is completed, the pressure is adjusted to the standard atmospheric pressure and the quartz substrate is removed to achieve negative pressure thermal transfer of the vertical array carbon nanocatalytic layer.

5. The controllable preparation method of a high current carrying multi-phase composite electrode with a vertical array carbon nanocatalytic layer as claimed in claim 4, characterized in that: The carbon source is camphor or sucrose.

6. The controllable preparation method of a high current carrying multi-phase composite electrode with a vertical array carbon nanocatalytic layer as claimed in claim 4, characterized in that: The mass ratio of carbon source to catalyst in step (2) is 8.3:

1.

7. The controllable preparation method of a high current carrying multi-phase composite electrode with a vertical array carbon nano-catalytic layer as claimed in claim 4, characterized in that: The catalyst is a metal catalyst with a particle size of 2nm to 20nm; the metal catalyst is ferrocene or cobalt iron oxide.

8. The controllable preparation method of a high current carrying multi-phase composite electrode with a vertical array carbon nano-catalytic layer as claimed in claim 7, characterized in that: The catalyst in step (2) is CoFeO2 nanoparticles.

9. The controllable preparation method of a high current carrying multi-phase composite electrode with a vertical array carbon nano-catalytic layer as claimed in claim 8, characterized in that: The preparation steps of CoFeO2 nanoparticle catalyst are as follows: (1) a mixture of 6-7 mM Fe(acac)3, 3-4 mM Co(acac)2, 25-30 mM 1,2-hexadecanediol, 18-20 mM oleic acid and 18-20 mM oleylamine is mixed with a solvent, wherein acac represents acetylacetone; (2) heating the mixture in a solvent from room temperature to 180-220° C. and stirring under inert gas protection; subsequently, stirring the obtained dark brown mixture at different reflux temperatures and continuously refluxing for different times, thereby obtaining CoFeO2 nanoparticles of different particle sizes; The reflux temperature was set to 263-300°C, the heating rate was set to 4-14°C, and the reflux time was 30-70 min to prepare a CoFeO2 nanoparticle catalyst with a particle size of 2nm-20nm; (3) After the reflux is completed, the mixture is cooled, the product is dissolved and centrifuged; (4) Drying the precipitate, which is the catalyst.

10. Use of the high current-carrying multiphase composite electrode with a vertical array carbon nanocatalytic layer as claimed in any one of claims 1 to 3 in improving the yield and current efficiency of in-situ electrocatalytic production of hydrogen peroxide or in coordinating with an ozone system to degrade pyridine.

Citation Information

Patent Citations

  • Bifunctional ordered membrane electrode of proton exchange membrane fuel cell

    CN111224137A

  • Magnetic graphene oxide-based metal-absorbing composite material and production process

    ES2844942A1

  • Improvements in or relating to ferrite particles and process for manufacturing same

    GB1142215A

  • Method for forming metal wiring and metal wiring board manufactured by the same

    JP2003298209A

  • Electrochemical double-layer capacitor using nanotube electrode structures

    US20120134071A1

Cited By

  • Titanium porous substrate composite electrode and preparation method thereof

    CN120006248A